An Optimized Method for Detecting Unauthorized Power Consumption. Issue 1 (23rd February 2023) - Mukhopadhyay, Sabyasachi; Sahni, Mohit; Chauhan, Adhiraj; Kumari, Nishi; Singh, Ram Chandra; Kumar, Manish; Alheety, Mustafa A.; Aldbea, Ftema W.
Abstract: Electrical energy plays an important role in the day‐to‐day life and backbone for the industries. Today life without electricity cannot be imagined. Because of the unnecessary actions taken by human beings, wastage and theft of power are increasing day by day. Theft of electricity is the criminal practice of stealing electrical power. It is a crime and is punishable by fines and/or incarceration. It belongs to the non‐technical losses. The objective of this work is to design a system that will try to minimize the illegal use of electricity and also reduce the chances of theft, and if theft happens appropriate actions will be taken. To identify and control power theft here, an intelligent system is introduced. It consists of two current transformers that are used to measure the actual load current and the other is to measure the turning back or neutral current. Those two current signals are fed to the micro controller. The micro controller will compare these two current signals. Depending on the comparison made by the micro controller it concludes whether power is theft through bypassing the energy.